Extraction of rice bran oil using subcritical carbon dioxide soxhlet - Chia, Siew Lian (2015)
Rice bran has been proven that it contains high amount of bioactive compounds such as vitamin E and γ-oryzanol and is recognized as source of healthy oil. To preserve these compounds in the final product, a good extraction method is needed. The current extraction method used in the industry involving hazardous chemicals such as hexane, which is toxic to human and environment. On the other hand, the supercritical fluid extraction method involving high temperature (50 - 80 C) and is a costly technology. A green extraction method that operates under lower temperature and lower cost is needed. The subcritical carbon dioxide Soxhlet (SCDS) extraction system, which operates at low temperature (28 ± 1 C), had used to extract rice bran oil in this study. Three samples of rice bran have been used: steam, hot-air stabilization and unstabilized rice bran (control). The extraction yields, contents of tocopherols, tocotrienols and oryzanol, fatty acid profiles; and the oxidative stabilities of the extracted rice bran oils were analyzed. The yields using hexane and SCDS extraction were approximately 22 % and 13 – 14.5 %, respectively. However, the oil extracted using the SCDS system contained approximately 10 times higher oryzanol and tocols compounds and lower free fatty acid levels and peroxide values compared with the hexane-extracted oil. While the steam stabilized rice bran gave the best oil quality relative to the others two samples. The steamed stabilized rice bran was chosen to be extracted using supercritical carbon dioxide extraction (SC-CO2) at 350 bar and 40 °C. The percentage oil yield extracted using SC-CO2 was 16.25 % in 200 minutes extraction time. However, the bioactive compounds in SC-CO2 extracted oil was even lower than hexane extracted oil. SCDS is a relatively new process, understanding and modeling of the extraction behavior is necessary. The extraction kinetics of rice bran oil and its bioactive compounds, namely, α-, β-, γ-, and δ-tocopherol; α-, γ-, and δ-tocotrienol; and γ-oryzanol, are discussed and correlated using the diffusion model (DM), logistic model (LM) and simple single plate model (SSPM). The extraction rate of the oil and active compounds was halved after 7 hours. After 15 hours of extraction, up to 95 % of the extractable active compounds were obtained. The SSPM is recommended for predicting the oil yield and oryzanol while LM is suitable to predict the tocopherols and tocotrienols in rice bran oil. In short, SCDS is a good extraction method, especially for the thermal labile compounds.